Quantitative Sputum Cell Counts to Monitor Bronchitis: A Qualitative Study of Physician and Patient Perspectives - Liesel D’silva; Helen Neighbour; Amiram Gafni; Katherine Radford; Frederick E Hargreave; Parameswaran Nair (Canadian Respiratory Journal)
Many common diseases affecting the airways are characterized by airway inflammation. The measurement of this inflammation has a significant role in the management of these diseases. Quantitative sputum cell counts provide a measurement of the type and severity of inflammation present. Sputum cell counts are used in routine clinical practice in some centres but their use is not widespread. The present study used a standardized questionnaire to determine both patients’ and physicians’ attitudes toward the use of sputum cell counts. The use of sputum cell counts was well accepted by patients and physicians. Ninety per cent of patients were satisfied with the test. Sixty per cent of family physicians were satisfied with the test and 80% were in favour of it being funded by the government. The authors recommend more widespread use of sputum cell counts to guide the management of airway diseases.